Museums During the COVID19 Pandemic: an Exploration of New Forms of Communication and Mediation of Artworks - Peverini, Paolo; Pezzini, Isabella (E|C, 2022)
The emergency situation generated by the pandemic is contributing to generate profound changes in museum institutions: forcing them to rethink objectives, explore new targets, experiment with new modes of communication, even to the point of reconsidering in some cases their overall positioning and identity. The impossibility of physical access to public spaces has contributed to accelerating a process of change in museums management, bringing back the focus of attention, for example, on the importance of the phatic dimension of signification, on the ability to generate, incentivize and maintain contact with visitors, profoundly rethinking spaces, times and modes of the museum experience. Many cultural institutions have responded to this profound and unexpected crisis by radically rethinking established modes of enunciation while transforming themselves into generators of new content In this context, forms of mediation of museums are marked by certain recurring characteristics: the multiplication of communication channels, the massive use of new technologies, with the use of short forms, narrativization and irony (see the case, famous and debated, of the opening of the TikTok channel of the Uffizi in Florence) the encouragement of playful use of artworks by users (#tussenkunstenquarantine), popularized by Google Art Culture but also taken over and institutionalized by landmark museums such as the Getty, the acceleration of the synergy between art and entertainment worlds with the possibility of enjoying artworks within gaming platforms such as Animal Crossing: New Horizons (MET, Getty, the National Museum of Science and Technology). The complex processes of renegotiating the meaning of institutions responsible for the preservation and promotion of works of art and the strategic role they play in the tourist destination market urge semiotics to explore the meaning-rich scenario of the new museums of our (new) present.